Mesocosm constructed wetland using heliconia psittacorum for wastewater treatment - Knicxkie Nathalie Unie, Frankie Bujang (2025)
Long-term micropollutant exposure harms humans and aquatic life, with caffeine affecting zebrafish neuromotor activity at 0.0006 mg/L. While Typha spp. is common in wetlands, monoculture systems may be less effective, emphasizing the need for more diverse treatment approaches. The primary objectives were to design the mesocosm constructed wetlands (CWs), evaluate properties of water in physio-chemical parameters and caffeine concentrations, and compare the performance of polyculture and monoculture systems of Heliconia psittacorum in terms of water quality, caffeine concentration, and plant analysis. Wastewater samples were collected and analyzed pre- and post-treatment for physiochemical parameter analyses (BOD, AN, TN), and the caffeine concentration in water was determined by using GC-FID. Plant analysis focused on chlorophyll estimation, lipid peroxidation, biomass allocation, water content, and nitrogen uptake. The physio-chemical properties of the treated wastewater showed greater improvement in polyculture systems in BOD reduction (70%), highlighting their advantage in enhancing overall water quality. H.psittacorum demonstrated equal caffeine removal efficiency oof 77.44% in wastewater treatment across both monoculture and polyculture systems. Plant analysis of H.psittacorum revealed minimal differences between the two systems (monoculture and polyculture), with high lipid peroxidation levels observed in both, indicating elevated oxidative stress, but high chlorophyll content in both systems indicates the best growth. However, H.psittacorum exhibited superior performance in nitrogen uptake in monoculture systems (3300 mg/kg) compared to polycultures (2800 mg/kg). These findings suggest that CWs with polycultures of ornamental plants can effectively combine aesthetic and functional benefits for sustainable wastewater treatment.